Utility of Forward-View Echoendoscopy for Transcolonic Fine-Needle Aspiration of Extracolonic Lesions: An Institutional Experience - Nithi Thinrungroj; Kazuo Hara; Nobumasa Mizuno; Takamichi Kuwahara; Nozomi Okuno (Korean Society of Gastrointestinal Endoscopy, 2020)
Background/Aims Non-invasive tissue sampling from the lower intra-abdominal and pelvic cavity is challenging. The role of endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA) in this situation is not well-established because of the limitations of the curved linear-array echoendoscopy-EUS for colonic insertion. The aim of this study was to report our institutional experience of transcolonic EUS-FNA using forward-viewing therapeutic linear echoendoscopy-EUS (FV-EUS) in combination with fluoroscopic guidance. Methods Medical records of 13 patients who underwent transcolonic EUS-FNA of extracolonic lesions using FV-EUS in combination with fluoroscopic guidance at Aichi Cancer Center Hospital, Nagoya, Japan from June 2015 to November 2018 were retrospectively reviewed. Results Using FV-EUS under fluoroscopic guidance, the FNA procedure could be performed successfully in all patients (100% technical success), with a median procedure time of 31 minutes. The sensitivity, specificity, and accuracy of EUS-FNA for detecting malignant lesions in this study were 91%, 100%, and 92%, respectively. There were no adverse events associated with the EUS-FNA procedure. Conclusions FV-EUS in combination with fluoroscopic guidance is an easy, safe, and effective technique for FNA of extracolonic lesions in the lower abdomen.